REE Recovery from End-of-Life NdFeB Permanent Magnet Scrap: A Critical Review - Yang, Yongxiang; Walton, Allan; Sheridan, Richard; Güth, Konrad; Gauß, Roland; Gutfleisch, Oliver; Buchert, Matthias; Steenari, Britt-Marie; Van Gerven, Tom; Jones, Peter Tom; Binnemans, Koen (Journal of sustainable metallurgy, 2017)
NdFeB permanent magnets have different life cycles, depending on the applications: from as short as 2–3 years in consumer electronics to 20–30 years in wind turbines. The size of the magnets ranges from less than 1 g in small consumer electronics to about 1 kg in electric vehicles (EVs) and hybrid and electric vehicles (HEVs), and can be as large as 1000–2000 kg in the generators of modern wind turbines. NdFeB permanent magnets contain about 31–32 wt% of rare-earth elements (REEs). Recycling of REEs contained in this type of magnets from the End-of-Life (EOL) products will play an important and complementary role in the total supply of REEs in the future. However, collection and recovery of the magnets from small consumer electronics imposes great social and technological challenges. This paper gives an overview of the sources of NdFeB permanent magnets related to their applications, followed by a summary of the various available technologies to recover the REEs from these magnets, including physical processing and separation, direct alloy production, and metallurgical extraction and recovery. At present, no commercial operation has been identified for recycling the EOL NdFeB permanent magnets and the recovery of the associated REE content. Most of the processing methods are still at various research and development stages. It is estimated that in the coming 10–15 years, the recycled REEs from EOL permanent magnets will play a significant role in the total REE supply in the magnet sector, provided that efficient technologies will be developed and implemented in practice.